PENGARUH PERMAINAN TRADISIONAL LEMPAR SANDAL TERHADAP KETERAMPILAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TK AISYIYAH V KOTA PEKANBARU - Nova Novelia; Wusono Indarto; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Basednon the result of observations in the field skills in the rough motor of children are not yet improve optimally. So, it is needed to apply traditional throw sandals game. This research of applying traditional throw sandals game to skills in the rough motor 4-5 years old children at Aisyiyah V kindergarten Pekanbaru City. The kind of this research is ekspriment with design on group pretest posttest design. Sample of this research are 15 children. Technique to college data is using observation. Technique of data analysis is using t-test with using SPSS 18.0 program. Based on the results obtained by testing the hypothesis tcount = 11,374 and Sig = 0,000 with ttable = 1,761 because tcount > ttable with taraf sig < 0,05. So, Ho refused and Ha accepted that means there are very significant different between before and after doing the game with traditional throw sandals game. Partly big the effect of traditional throw sandals game toward skills in the rough motor 4-5 years old children at Aisyiyah V kindergarten Pekanbaru City amount to 63,91%.Key Words: Skills Rough Motor, Throw Sandals